Sinergi Lintas Universitas dalam Pendampingan Literasi Pupuk Mandiri dan Perlindungan Hak Petani untuk Mewujudkan Kedaulatan Pangan - Muhammad Ahwan; Agus Suryanto; Tri Rahayuningsih; Sunarso Sunarso; Suyani Suyani; Dyah Erlina Sulistyaningrum; Tri Rettagung Diana; Wildan Nur Hidayatullah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2026)
This community service program aims to enhance farmers’ literacy on independent fertilizer production and strengthen their understanding of farmers’ rights within national fertilizer governance as an effort to achieve food sovereignty. The program was implemented in Belang Village, Bungkal Sub-district, Ponorogo Regency, involving GAPOKTAN Baungan consisting of farmer groups from Tempel, Kepuh, Pakal, Kanigoro, and Klatakan hamlets. This initiative represents cross-university synergy involving lecturers from Universitas Merdeka Malang, Universitas Soerjo Ngawi, Universitas Muhammadiyah Ponorogo, and Akademi Kesejahteraan Sosial Ibu Kartini Semarang. The implementation adopted a participatory hybrid approach combining Zoom Meeting dissemination and offline field activities. Activities included literacy enhancement on independent fertilizer production, training on organic fertilizer processing, strengthening farmer group institutions, and legal literacy regarding farmers’ rights in accessing subsidized fertilizers, including RDKK mechanisms and national policies. Methods comprised participatory socialization, hands-on training, group discussions, field practice, and monitoring and evaluation. Results show improved understanding of independent fertilizer concepts, increased technical skills in organic fertilizer production, and greater awareness of farmers’ rights and obligations in the fertilizer distribution system. The program strengthened inter-university collaboration and farmer networks, supporting sustainability, farmer independence, reduced dependence on chemical fertilizers, and community-based food sovereignty.